A semi-industrial reactor for producing biodiesel from waste cooking oil. Issue 4 (21st April 2023) - Ibrahim, Said M. A.; Abed, K. A.; Gad, M. S.; Abu Hashish, H. M.
Abstract: This work offers a pilot plant unit designed to produce biodiesel efficiently from waste cooking oil (WCO). The quality of biodiesel from the semi-industrial plant met American Society of Testing and Materials (ASTM) standards with a maximum yield of 71.56%. Many biodiesel samples were tested, but the highest yield was 71.56%, achieved with a mixing speed of 200 rpm, 20% methanol/oil ratio, reaction time of 90 min, reaction temperature of 70 °C, and catalyst concentration of 1%. The fatty acids in WCO were palmitic, oleic, and linoleic, 5.13, 37.22 and 7.66%, but for biodiesel they were 5.1, 26.16 and 49.51%, respectively. Thermal gravimetric analysis and Thin-layer chromatography confirmed the formation of biodiesel. The ester is in the range of 1741:2823 cm −1, which is related to the stretching band of C = O. The physicochemical properties agreed with ASTM standards. The biodiesel yield is significantly affected by the quality of the used WCO. The results indicate the significant effect of purity, quality, cooking temperature and cooking time of the used oil on biodiesel yield. A high yield of 94.5% was obtained for high-quality oil that was slightly heated for no cooking time. The designed pilot plant is efficient and reliable at producing biodiesel from WCO.